Serbia - Country Economic Memorandum : The Road to Prosperity - Productivity and Exports, Volume 2. Main Report - World Bank (World Bank, 2012)
This report looks beyond the current global financial crisis to the restoration of dynamic long-run growth in Serbia. The answer in this report is that Serbia will need to fundamentally alter its growth model to compete effectively in world markets. The past model relying on excessive inflows of capital and credit that, in part, fuelled a consumption boom has run its course in all European countries. Serbia must shift to a greater export orientation so that it can attain the major gains in productivity and competitiveness necessary to propel economic growth to a much higher trajectory. This cannot happen without an explicit export strategy, and a set of concomitant structural reforms, driven by commitment and coordination at the highest political level. This report tries to pinpoint policy actions that would be most effective in raising the rate of productivity growth of Serbia s enterprises so that better export performance and sustained growth could be achieved. The report has three parts. Part I reviews Serbia s macroeconomic situation and its progress on structural reforms. Part II starts with a review of the current status of Serbia s exports and trade policy and regional trade arrangements. It then uses product space (PS) analysis to examine areas where Serbia has a revealed or potential comparative advantage. The report then moves on to two such areas, metal processing and automobile production, which are subjected to value chain analysis to identify bottlenecks that need to be removed for Serbia to become a successful producer and exporter in these areas. The final part of the report looks at obstacles to more rapid and sustainable development of production and exports. It starts with the analysis of the business environment, based on a range of surveys, which is followed by four sectoral chapters that discuss the obstacles found to be most binding in the business environment: labor skills, power supply and efficiency of its use, use of land, and trade facilitation.